The probiotic strain Shewanella putrefaciens Pdp11 strongly modulates gene expression of the fish pathogen Vibrio harveyi - Delgado-Martín, Belén; Cerezo Ortega, Isabel M.; Domínguez-Maqueda, Marta; Bautista-Moreno, Rocío; Claros-Díaz, Manuel Gonzalo; Tapia-Paniagua, Silvana Teresa; Balebona-Accino, María del Carmen; Moriñigo-Gutiérrez, Miguel Ángel (My University, 2022)
In this work, the interaction between the fish probiotic Shewanella putrefaciens Pdp11 and the fish pathogen V. harveyi was studied by RNA-seq to understand how SpPdp11 interferes with the pathogen through bioinformatics analysis. Three types of cultures were performed: SpPdp11 alone, V. harveyi alone and SpPdp11 and V. harveyi together. RNA was extracted and sequenced (paired end, 2x75 bp) at the Ultrasequencing Service of the University of Málaga using the Illumina NextSeqTM 550 platform. Raw reads were processed using a bioinformatic pipeline and a network analysis was performed for the most relevant functional enrichment results. The results suggest that the presence of SpPdp11 affects V. harveyi to a greater extent than V. harveyi affects SpPdp11. Considering that V. harveyi is a pathogenic strain and SpPdp11 is a probiotic strain, this may be positive for its probiotic capacity, as it not only maintains its functionality almost intact, but also produces a huge imbalance in that of V. harveyi
Keywords: Peces -- agentes patógenos; Microbiología marina; Acuicultura; Probióticos; Patógenos; RNA-seq